Caracterização de manteiga caprina adicionada de cúrcuma (Curcuma longa L.): avaliação do potencial antioxidante - Oliveira, Maria Juliete da Silva (2018)
The industrialization of goat's milk has been growing stronger, given its technological and nutritional potential. However, commercialization of goat butter is still scarce, most probably due to its richness in short chain and unsaturated fatty acids, susceptible to both hydrolytic and oxidative rancidification processes. The food industry has made use of various food additives, be they synthetic and / or natural with antioxidant properties in order to protect the lipids from deterioration, and avoid sensorial losses and damages to the health of the consumer. Among the possible natural antioxidants available, we can mention turmeric (Curcuma longa L.), which is a condiment used since antiquity in the preparation and preservation of food. Thus, the objective of this study was to develop caprine butter added with different concentrations of turmeric (Curcuma longa L.), to characterize its physicochemical, microbiological and sensorial aspects, as well as to evaluate the thermal stability of goat butter and the antioxidant potential of the of the aforementioned spice on butter during refrigerated storage. For this, 3 formulations of goat butter were prepared, being MC - Control goat butter, without addition of turmeric; M1,5% - Caprine butter containing turmeric at a concentration of 1,5% and M3% - Caprine butter with 3% turmeric. In the turmeric the identification and quantification by HPLC of the phenolic compounds were carried out and in the butters were carried out the tests of determination of pH, acidity in oleic acid, humidity, proteins, lipids, total phenolic compounds, antioxidant activity, fatty acid profile, thermal stability, as well as microbiological and sensory analyzes. The shelf life of the formulations was analyzed at 1, 30 and 60 days refrigerated storage (4 ± 1 ° C). In general, it was observed that the addition of different concentrations of turmeric did not influence most of the physical and physicochemical characteristics of the samples. There was an increase in phenolic compounds and antioxidants in butters, influenced by the concentration of added turmeric. The increase in turmeric concentration was positively associated with the thermal stability of the samples. In sensory terms, all goat butter were well accepted until the end of shelf life, with no added turmeric influence in accepting most of the evaluated attributes. The results confirm the potential of the use of turmeric in caprine butter as a preventive measure of lipid oxidation during storage, with an increase in its thermal stability and positive repercussions on technological, nutritional and sensorial qualities.